PENGARUH ARUS KAS, LABA AKUNTANSI, UKURAN PERUSAHAAN, DAN RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021- 2023 - Denisa Sinaga; Delvi Yani Lase; Ayu Andari; Muhammad Habibie (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this study is to determine the effect of cash flow, accounting profit, company size, and return on assets (ROA) on stock returns in manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. This study uses multiple linear regression analysis methods to test the effect of each variable on stock returns. The research sample was taken from secondary data in the form of financial reports of manufacturing companies published by the IDX during the period 2021-2023. The results of the study indicate that partially, cash flow and return on assets (ROA) do not have a significant effect on stock returns. Conversely, accounting profit and company size have a positive and significant effect on stock returns. Meanwhile, ROA does not have a significant impact on stock returns. This study is expected to contribute to investment decision making by investors, as well as be a consideration for companies in increasing company value through optimization of accounting profit and growth in company size.